Novel Techniques to Enhance the Security of Smartphone Applications - Dar, Muneer Ahmad; Parvez, Javed (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Smart phones have already become an important part of our lives. Smartphone is in the hands of millions of novice users who are unaware of the security concerns they may face. In order to address the security concerns of the millions of users, we propose and implement three novel techniques to enhance the security of these Smartphone’s. The first Technique is Need based Security (NBS) wherein we take away the flexibility from the programmer and give the control to the users who can decide whether to permit the application to access any of the resources or not. In our second Technique we used the security API which will take care of everything in background and in our third technique we locked all the applications so that they can be restricted from doing any malicious activity. We tried to find out the security loopholes in one of the leading Smartphone operating system i.e. Android with the intension to apply the novel techniques proposed and implemented in this paper.